SPERANŢA FARCA, REMEDIES FOR FEAR OF THE UNKNOWN. BUCHAREST, EDITURA UNIVERSITARĂ PUBLISHING HOUSE, 2020, 269 PAGES, ISBN 978-606-28-1168-6 - Andreea-Diana SCODA (National Centre for Policy and Evaluation in Education, 2021)
Book review